1998
DOI: 10.1002/macp.1998.021990809
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal crystallization kinetics of compatibilized blends of polyolefines with a semiflexible liquid crystalline polymer

Abstract: SUMMARY A study of the isothermal crystallization behaviour and an analysis of the kinetic parameters of compatibilized blends of polyolefines (isotactic poly(propy1ene) (iPP) and high density polyethylene (HDPE)) with a semiflexible liquid crystalline polymer (LCP) SBH 1 : 1 : 2 of Eniricerche, Italy are presented in this work. The compatibilizers are ad hoc synthesized graft copolymers of the liquid crystalline polymer grafted to functionalized poly(propy1ene) (PPAA) or polyethylene (PEox) -PP-g-SBH and PE-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The kinetics parameters of isothermal crystallization were determined by the following modified Avrami equation:1, 2, 4, 5, 14–21 where X ti is the relative crystallinity at crystallization time t i , K is a crystallization kinetic constant, and n is the Avrami exponent.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetics parameters of isothermal crystallization were determined by the following modified Avrami equation:1, 2, 4, 5, 14–21 where X ti is the relative crystallinity at crystallization time t i , K is a crystallization kinetic constant, and n is the Avrami exponent.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature was gently allowed to rise until 0°C for 5 min, and after all the CuCN was dissolved, the system was cooled to -78°C and 8 mL of trans-2-nonenal (48.3 mmol) was added. After stirring for 1 h at -78°C the reaction mixture was quenched with a 10% solution of NH 4 Cl/NH 4 OH, extracted with diethyl ether and dried over Na 2 SO 4 . After solvent evaporation, the product was purified by flash chromatography on silica gel using pentane/diethyl ether 9:1 as eluent.…”
Section: -Butylnonanalmentioning
confidence: 99%
“…Increasingly important applications of these systems are modern opto-electronic materials formed by host olefin polymers blended with highly conjugated guest polymers, aromatic or inorganic molecules [1]. In addition, chain orientation and extension of the host polymer system can also be used to generate and to enhance for instance the optical [2], electrical [3] and thermal [4] properties of the binary devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the thermoplastic polymer is semicrystalline, such as iPP, even low levels of LCP can significantly affect the morphology and the blend properties. This is because the complex crystallization behavior of this type of system depends on the influence of the dispersed component on the nucleation of the polymer matrix 21–24. It has been widely observed that the crystallization of iPP generally occurs on the surface of heterogeneities.…”
Section: Introductionmentioning
confidence: 99%